Tailoring Self-Help Mindfulness and Relaxation Techniques for Stroke Survivors: Examining Preferences, Feasibility and Acceptability - Wang, Xu; Smith, Connie; Ashley, Laura; Hyland, Michael E. (Frontiers in Psychology, 2019)
Objective: Studies on psychological techniques to reduce stroke-related anxiety and/or distress are limited. More scarce is research on tailoring such techniques to suit stroke survivors’ needs, including the needs of those with aphasia. To address this gap, we report two sequential studies. Study 1 explored preferred psychological techniques (i.e., mindfulness and relaxation) and ways to modify them for stroke survivors, including those with communication difficulties. Study 2 examined the feasibility and acceptability of these modified techniques with a new sample of survivors. Design: Mixed-methods using qualitative and quantitative approach in both studies. Participants: All participants were stroke survivors living in the community (Study 1: n = 13, median age = 61 years; Study 2: n = 38, median age = 67 years). Interventions and Procedures: Study 1: seven techniques representing commonly used types of mindfulness and relaxation were filmed on a professionally produced DVD. Participants feedback on how these techniques could be tailored to meet their needs, their preferences for techniques and reasons for likes and dislikes. Study 2: four favored techniques from study 1 were modified and re-filmed into a new DVD. A new group of participants were asked to practice them twice daily, five times a week for at least 4 weeks. They completed questionnaires at the start of the study (T1), returned approximately 4 weeks later completing the same measures (n = 24 at T2). Focus group discussions/interviews were conducted at the end of T2 exploring the feasibility and acceptability of these techniques. Results: Four techniques were favored by participants in Study 1. After adaptation, these techniques were generally perceived as acceptable, user-friendly and beneficial to participants who participated in the focus groups /interviews in Study 2. A ‘once a day’ practice frequency could make practicing more feasible. Participants also preferred having choices- multiple techniques could be more useful than single technique. Conclusion: Tailoring psychological techniques for stroke survivors is beneficial. Tailored techniques in a self-help DVD format seemed feasible and acceptable, however, a less frequent practice would be easier for stroke survivors. Future studies should seek to recruit a more heterogenous sample as well as implementing strategies to increase the retention rate.